Economic Contributions of Agriculture, Natural Resources, and Related Food Industries in Florida in 2012 - Alan W. Hodges; Mohammad Rahmani; Thomas J. Stevens (EDIS)
Agriculture, natural resources, and related food industries remain a significant force in the economy of Florida, and it is important to recognize their economic contributions for informed public policy. The economic contributions of these industries were re-evaluated for calendar year 2012 to update previous reports and to provide current information on economic trends in the wake of the historic global recession of 2007–2009. This 116-page report was written by Alan W. Hodges, Mohammad Rahmani, and Thomas J. Stevens, and published by the UF Department of Food and Resource Economics, July 2014.